2011
DOI: 10.1136/bjsm.2010.081554.12
|View full text |Cite
|
Sign up to set email alerts
|

Injuries patterns among professional golfers: an international survey

Abstract: BackgroundGolf is a popular sport played worldwide. The majority of professional golfers work as teaching professionals based at golf clubs. All professional players spend numerous hours on the golf course, placing themselves at increased risk of injury. There have been no recent, large studies investigating injury patterns among male and female professional golfers.ObjectiveTo investigate the frequency, types and mechanism of injury sustained by male and female professional golfers and to compare injury patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…115–118 Prospective longitudinal studies report very low injury rates compared to other sports, at 0.28–0.60 injuries per 1000 hours in amateurs 57109 119 Professionals play more, and are injured more frequently, with annual injury rates of between 31.0% and 90.0%,115 120 and quoted lifetime incidence of 60.0–88.5%. Overall, the incidence of injury is moderate, and the rate of injury per hour played is low.…”
Section: Thematic Summarymentioning
confidence: 99%
“…115–118 Prospective longitudinal studies report very low injury rates compared to other sports, at 0.28–0.60 injuries per 1000 hours in amateurs 57109 119 Professionals play more, and are injured more frequently, with annual injury rates of between 31.0% and 90.0%,115 120 and quoted lifetime incidence of 60.0–88.5%. Overall, the incidence of injury is moderate, and the rate of injury per hour played is low.…”
Section: Thematic Summarymentioning
confidence: 99%
“…Many professional athletes' careers are impacted by sports-related and nonsportsrelated injuries [17][18][19]. This study did not consider how the careers of the players on the JLPGA Tour are affected by injuries due to a lack of the appropriate data.…”
Section: Discussionmentioning
confidence: 99%
“…16 JLPGA adopted the tour system (LPGA of Japan Tour) in 1988. 17 Over the past three decades, the JLPGA Tour has been steadily internationalized in terms of both the composition of the players on the tour and the movement of players to the LPGA Tour for international competition outside Japan. For the 2020 season, 17 of 65 players on the priority list were internationals.…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Examining the Influence of Different Grip Types on Wrist and Club Head Kinematics during the Golf Swing: Benefits of a Local Co-ordinate System Wrists movements have been identified as an important factor in the production of a successful golf swing, with their complex range of motion (ROM) influencing both club head velocity and orientation (Nesbit, 2005;PGA, 2008;Sprigings & Neal, 2000). They have also been identified as having the greatest angular velocities of all joints during the golf swing (Zheng, Barrentine, Fleisig, & Andrews, 2008) and are consistently reported as the primary injury site, particularly in the lead wrist (left in right-handed golfers), amongst high-level golfers (Barclay, West, Shoaib, Morrissey, & Langdown, 2011;McCarroll, Retting, & Shelbourne, 1990). For example, Barclay et al reported within an international survey of 526 club and touring professionals a 66% prevalence of injury and within that sample a 44% incidence rate pertaining to the wrist.…”
mentioning
confidence: 99%